(untitled) (International Journal of Innovative Technologies in Economy, 2022)
Agriculture is the most important branch of the country’s economy, the main purpose of which is to ensure food self-sufficiency. In this respect, it is considered sponsored in almost all countries of the world; governments promote the development of agriculture with various state support tools. More than a dozen programs aimed at the development of the agricultural sector are implemented in Armenia. The article has studied in detail the programs implemented in the field of agriculture in the last 3 years, and further program proposals for the development of agriculture are presented.